DEVELOPMENT AND INITIAL VALIDATION OF THE MULTIDIMENSIONAL SOCIAL CAPITAL SCALE (MSCS) - Ozerska, Inta; Šuriņa, Sanita; Perepjolkina, Viktorija; Akmane, Elīna; Mārtinsone, Kristīne (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
Social capital has been studied as one of the most important external resources that contribute to overcoming difficulties of individuals, the ability to adapt and show solidarity in times of crisis, preventive behavior. However, no specific assessment tool has been developed and validated for the measurement of social capital in Latvian. The present study aimed to develop and perform an initial validation of the Multidimensional Social Capital Scale (MSCS) in a Latvian adult sample. The developed theoretical concept based on rapid review covers such types of social capital as bonding, bridging and linking, and there are two dimensions in each of these types: cognitive and structural. Data were collected from a representative sample of Latvian inhabitants (N=1003), within a framework of the National research program “Life with COVID-19” in September 2020. As a result, a four-component structure was obtained. MSCS covers only the cognitive dimension of all three types. One type of bonding (Shared values and perceived social support for family members and close friends), one type of bridging (Perceived social support for friends and acquaintances), and two types of linking (Institutional trust and Attitude towards laws and norms). The items are internally consistent on all scales (Cronbach’s alpha ranged from .80 to .90). Discrimination indices generally meet the scientific requirements falling within the range (.20 – .80). Based on Exploratory (EFA) and Confirmatory factor analysis (CFA) a four-factor structure of MSCS was confirmed (k = 16) in two samples. CFA results demonstrated that the MSCS was a valid and reliable multidimensional scale, which was invariant across both samples. The present findings indicate the validity and reliability of the MSCS for the Latvian population.